Can dialectical behavior therapy skills group treat social anxiety disorder? A brief integrative review - Villalongo Andino, Mara; Garcia, Katelyn M.; Richey, John A. (Frontiers in Psychology, 2024)
The purposes of this brief integrative review are to identify and critically evaluate recent work in the area of Dialectical Behavior Therapy-Skills Group (DBT-SG) for Social Anxiety Disorder (SAD) with suicidal ideation (SI) and to suggest further how DBT-based skills may be applied to cognitive maintenance factors of SAD. Accordingly, we first evaluate the relevance of DBT in treating SI in other disorders. Second, we evaluate the relationship between SI and SAD, providing considerations for the complexity of comorbid disorders and presentations. Finally, we extend this knowledge to discuss considerations for the use of DBT-SG skills to target specific etiological and maintenance elements of SAD, with a focus on four themes (interpersonal effectiveness, mindfulness, emotion regulation, and distress tolerance). Overall, we conclude that DBT-SG may prove beneficial in reducing SI and symptoms in SAD that impact social and emotional functioning.